ANALISIS PENGARUH CUSTOMER FOCUSED SERVICE TERHADAP MINAT NASABAH PADA PRODUK BERJANGKA: DEPOSITO, TABUNGAN PRIMA BERHADIAH DAN TABUNGAN RENCANA BERHADIAH) DI BANK MUAMALAT INDONESIA KCU PONDOK INDAH - Elgita Arum Dwiyanti; Siti Nur Azizah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2018)
Customer focused service is a strategy implemented by the company in order to serve customers as well as possible. The shape of this strategy measured by the quality of service provided by the company to customers. The factors that determine the level of success and quality of the company is the ability of the company in providing services to customers. This study was conducted to determine the effect of service quality on customer interest in product futures at Bank Muamalat Indonesia KCU Pondok Indah. The independent variable in this research is service quality which consist of tangible, reliability, responsiveness, assurance, empathy and compliance, while the dependent variable is customer interest. The sampling technique using simple random sampling. Data collection using questionnaires with a total sample of 70 respondents who visited customer service at Bank Muamalat Indonesia KCU Pondok Indah. Data analysis used descriptive analysis and multiple linear regression analysis. The results of this study indicate that simultaneously the quality of service has a significant effect on customer interest in the futures product at Bank Muamalat Idonesia KCU Pondok Indah. Partial result shows that variable of reliability, responsiveness, empathy and compliance have significant influence to interest, while tangible and assurance variable have no significant effect to customer interest in product of futures at Bank Muamalat Idonesia KCU Pondok Indah.Keyword: Customer focused service, service quality, customer interest, product fitures